Meningkatkan Kinerja Usaha Umkm Dengan Strategi Keunggulan Bersaing Dan Pemasaran Online Di Yayasan Rumah Marketer Sahabat Qur’an Pengasinan, Sawangan - Depok - Silvia Sari; Rini Septiowati; Purwatiningsih Purwatiningsih (Universitas Pamulang, 2022)
The main problem faced by business actors is the lack of knowledge in marketing both conventionally (offline) and online, especially e-commerce and lack of knowledge about competitive strategies. The lack of knowledge of business actors regarding competitive strategy and digital marketing inspired the community service team to deliver outreach and provide training on the web and networks to be able to expand their business. The community service entitled Improving MSME business performance with competitive advantage strategies and online marketing at the Rumah Marketer Pengasinan Foundation, Sawangan Depok aims to provide an introduction to digital marketing, invite and instill awareness among MSME actors that it is very important to develop marketing through digital marketing to can increase income and survive the pandemic during the recovery transition after covid. The target of this service is MSMEs in the city of Depok - West Java. The results of this PKM have proven that MSME players can master sales methods through e-commerce and digital marketing so they can survive the recovery period after the Covid-19 pandemic.